INVESTIGATING LIBYAN CONSUMERS’ ACCEPTANCE TOWARDS GREEN PURCHASING CONCEPT - Abdulsatar Fathe G. Il Tohame; Genoveva Genoveva (UNIVERSITAS PAKUAN, 2021)
Green purchasing concept adoption witnessing a rapid increase according to recent researches, not to mention that, environmental issues have been trending in the last few decades as well, and according to previous researches, a lack of literatures regarding this issue in Libya were found after searching around the country’s biggest universities such as Tripoli University, Benghazi University, and Misurata University. This study used quantitative research method aiming to investigate the strongest variables affecting the Libyan consumers’ acceptance towards the concept of green purchasing among three different categories of variables, environmental knowledge, cultural beliefs and price sensitivity, as Libya is showing a very slow growing in adopting the concept of green purchasing, hence, conducting such a study is an essential role-play in highlighting the strongest factors affecting the adoption of the concept amongst Libyan consumers. The data was collected via distributed Google form, and a sample of 700 respondents were collected to be analyzed using SPSS 0.25. Accordingly, findings showed the significant affect that environmental knowledge and cultural beliefs severally have on Libyan consumers’ acceptance towards green acceptance, at a variance to price sensitivity which showed insignificant effect. Moreover, environmental knowledge, cultural beliefs and price sensitivity concurrently affected the acceptance of Libyan consumers’ acceptance towards green purchasing.